1995
DOI: 10.1515/hfsg.1995.49.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Metal Ion Content of Material Removed from the Surface of Unbleached Kraft Fibres

Abstract: Distribution and attachment of metal ions to the pulp components in krafl pulps can a fleet the possibilities to achieve a metal ion profile favourable for total chlorine free bleaching. By enrichment and analysis of different morphological fractions of the pulp, such as material from the fibre surface and ray cells, the metal ion distribution (Fe, Cu, Mn, Mg and Ca) in a commercial unbleached softwood kraft pulp (kappa number 32) was investigated. Material removed from the surface of unbleached kraft fibres a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…It has been shown that MnP plays an important role in the bleaching of unbleached hardwood kraft pulp by white rot fungi (15,17,19,23,33). Although the manganese ion which is necessary for the MnP catalytic system is present in the kraft pulp (14,16,33), the pulp was not substantially brightened unless MnSO 4 was added during in vitro bleaching with MnP in 50 mM malonate buffer (pH 4.5), as previously reported (22). The oxidation of Mn 2ϩ by MnP is dependent on the presence of organic acids produced by the fungus.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that MnP plays an important role in the bleaching of unbleached hardwood kraft pulp by white rot fungi (15,17,19,23,33). Although the manganese ion which is necessary for the MnP catalytic system is present in the kraft pulp (14,16,33), the pulp was not substantially brightened unless MnSO 4 was added during in vitro bleaching with MnP in 50 mM malonate buffer (pH 4.5), as previously reported (22). The oxidation of Mn 2ϩ by MnP is dependent on the presence of organic acids produced by the fungus.…”
Section: Discussionmentioning
confidence: 99%